The association between season of birth, age at onset, and clozapine use in schizophrenia. (25th July 2017) - Kim, J. S; Park, C. M.; Choi, J. A.; Park, E.; Tchoe, H. J.; Choi, M.; Suh, J. K.; Kim, Y. H.; Won, S. H.; Chung, Y. C.; Bae, K. Y.; Lee, S. K.; et al.
Abstract : Objective: This study aimed to determine whether the rate of clozapine use, an indicator of refractoriness in schizophrenia, is associated with the season of birth and age at onset in patients with schizophrenia based on nationwide data. Methods: Patients with schizophrenia ( n = 114 749) who received prescriptions for antipsychotic medication between 2008 and 2014 were retrospectively identified from the Korean National Health Insurance Service database. The study population was divided into three groups based on their age at the onset of schizophrenia (early, middle, and late onset). We assessed differences in the month of birth between patients and the general population. In addition, the cumulative clozapine use was calculated. Results: Compared to the late‐onset schizophrenia group, the early‐ and middle‐onset groups showed a higher probability of birth during the winter season. In addition, the early‐onset group showed the highest cumulative clozapine use rate. In the middle‐onset group, the initiation of clozapine use was significantly earlier for patients born in winter compared to those born in summer. Conclusion: Our results indicate that the age at onset is an important factor in predicting the prognosis of schizophrenia patients. The season of birth also affects the prognosis, but with less robustness. Specifically, it appears that early disease onset and winter birth might be associated with poor outcomes in Korean patients with schizophrenia.